(untitled) (Web of Medicine: Journal of Medicine, Practice and Nursing, 2025)
Therapeutic practice plays a pivotal role in the diagnosis and management of internal diseases by serving as a bridge between clinical observation and evidence-based decision-making. As internal diseases often present with complex, overlapping symptoms, a comprehensive therapeutic approach enables clinicians to refine diagnostic accuracy through continuous patient assessment, response monitoring, and interdisciplinary collaboration. This article explores how therapeutic strategies not only support symptom control and disease management but also contribute directly to diagnostic clarification through individualized treatment responses and functional evaluations. By emphasizing a holistic, patient-centered model, this paper advocates for the integration of therapeutic insights into diagnostic pathways, highlighting their value in improving clinical outcomes, enhancing patient satisfaction, and fostering more precise and timely medical decisions.